Gambling-related harm as a function of gambling involvement in the Icelandic public: Examining potential thresholds for Low-Risk Gambling Guidelines - Arndís Eva Finnsdóttir 1993- (2020)
The aim of this study was firstly to explore the association between gambling involvement and harm in the Icelandic public and to evaluate the use of Receiver Operating Characteristic (ROC) curve for analyses selecting quantitative limits of gambling involvement, as proposed by Currie et al. (2006). The analyses were based on unweighted data collected in comprehensive computer-assisted telephone interviews on the gambling behaviour of 2,045 Icelandic gamblers in 2017. Gambling involvement was assessed via five different measures of frequency (days per month), absolute expenditure per month, expenditure of income, number of gambling types, and number of continuous/skill-based gambling types. Associations between gambling involvement and five domains of harm were mapped using risk-curves and risk ratio. Based on the ROC curve analyses, low-risk gambling limits were suggested. The risk curves indicated that risk of harm increased with gambling involvement, although moderate gambling levels were associated with little or no increase in. The overall classification accuracy of gambling involvement was moderate to good (AUC = .74-.94) and the ROC curves provided the following cut-offs for: expenditure, spending no more than 5,046 to 11,636 isk per month a month and for expenditure of income 0.75% to 1.47%. For gambling frequency, the analysis suggested not gambling for more than 4 to 5 days a month and for number of gambling forms to restrict participation to 4 to 5 and for continuous/skill-based gambling forms to 2 forms in 12 months. Conclusions: Gambling involvement, as estimated by expenditure, frequency and number of gambling forms, is associated with gambling harm and ROC curve analyses are a useful tool to estimate quantitative gambling limits for the general public in Iceland. Issues concerning the development and application of low-risk gambling guidelines are discussed.